2019
DOI: 10.1016/j.jssr.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Elementary Social Studies during Snack Time and other Unstructured Spaces

Abstract: It is common practice for social studies in the elementary school day to be integrated into other subject areas, especially language arts. Also common in an elementary school day are unstructured spaces such as snack time or recess. In this paper, we present findings from a larger study on social studies integration within various subject areas to explore how two teachers (first and fifth grade) integrated social studies into unstructured spaces. These teachers integrated social studies concepts and experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In some cases, the social studies was immediately apparent to students while, in some instances, the connections to social studies concepts and content was less obvious. Over the course of 26 observations in two different schools, we observed social studies integrated into nearly every subject area as well as during non-academic times such as morning transitions or snack time (See Table 2) (Whitlock & Brugar, 2019). Although it would appear to be good news that social studies is observed so often, the quality of social studies matters more than the quantity (Table 5).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In some cases, the social studies was immediately apparent to students while, in some instances, the connections to social studies concepts and content was less obvious. Over the course of 26 observations in two different schools, we observed social studies integrated into nearly every subject area as well as during non-academic times such as morning transitions or snack time (See Table 2) (Whitlock & Brugar, 2019). Although it would appear to be good news that social studies is observed so often, the quality of social studies matters more than the quantity (Table 5).…”
Section: Discussionmentioning
confidence: 97%
“…In the case of these two classrooms, we did not limit examples of social studies integration to only language arts lessons. In fact, we found social studies content being "taught" during non-academic times such as snack time or morning meeting (Whitlock & Brugar, 2019).…”
Section: Stealthy Integrationmentioning
confidence: 92%
See 1 more Smart Citation
“…Based on the objectives of Social Studies in Nigerian schools, the emphasis of the subject is more on social phenomena (inductive) than theory (deductive). Social Studies is a field of knowledge and analysis of social symptoms and problems to find solutions to emerging issues and problems in the society (Whitlock & Brugar, 2019;Ollila & Macy, 2019). Therefore, Social Studies learning in schools must emphasize aspects of knowledge, attitudes, and skills from various contextual social problems that exist around students.…”
mentioning
confidence: 99%